Exploring new strategies in diseases resistance of horticultural crops - Xu, Jun; Zhang, Ningyuan; Wang, Ke; Xian, Qianqian; Dong, Jingping; Chen, Xuehao (Frontiers in Sustainable Food Systems, 2022)
Horticultural crops are susceptible to various biotic stressors including fungi, oomycetes, bacteria, viruses, and root-knot nematodes. These pathogens limit the growth, development, yield, and quality of horticultural crops, and also limit their adaptability and geographic distribution. The continuous cropping model in horticultural facilities exacerbates soil-borne diseases, and severely restricts yield, quality, and productivity. Recent progress in the understanding of mechanisms that confer tolerance to different diseases through innovative strategies including host-induced gene silencing (HIGS), targeting susceptibility genes, and rootstocks grafting applications are reviewed to systematically explore the resistance mechanisms against horticultural plant diseases. Future work should successfully breed resistant varieties using these strategies combined with molecular biologic methods.